From the World's Four Corners - National Paint, Varnish (Pamphlets corresponding to radio shows produced by the National Paint, Varnish and Lacquer Association, 1940)
Booklet corresponding to a radio broadcast program created in cooperation with Foreign Trade week by the National Paint, Varnish, and Lacquer Association. The booklet describes how components of all paint products hail from all over the world. Discusses the origins of shellac, exterior paint pigments, linseed oil, oiticica, perilla oil, and gums and resins. Includes small stylized illustrations throughout, and decorated covers with a world map design. Two illustrations depict racially-stereotyped imagery of Indian people. The National Paint, Oil and Varnish Association, Inc., formed in 1933, was the national professional association representing all branches of the paint, oil, and varnish industries.
Keywords: Shellac; Paint materials; Linseed oil; Varnish and varnishing; Varnish industry; Paint industry and trade; Pigments; International trade; Stereotypes (Social psychology); Racism